Evolution of the therian face through complete loss of the premaxilla. Issue 1 (26th August 2022) - Higashiyama, Hiroki; Koyabu, Daisuke; Kurihara, Hiroki
Abstract: The anatomical framework of the jawbones is highly conserved among most of the Osteichthyes, including the tetrapods. However, our recent study suggested that the premaxilla, the rostralmost upper jaw bone, was rearranged during the evolution of therian mammals, being replaced by the septomaxilla at least in the lateral part. In the present study, to understand more about the process of evolution from the ancestral upper jaw to the therian face, we re‐examined the development of the therian premaxilla (incisive bone). By comparing mouse, bat, goat, and cattle fetuses, we confirmed that the therian premaxilla has dual developmental origins, the lateral body and the palatine process. This dual development is widely conserved among the therian mammals. Cell‐lineage‐tracing experiments using Dlx1 ‐CreER T2 mice revealed that the palatine process arises in the ventral part of the premandibular domain, where the nasopalatine nerve distributes, whereas the lateral body develops from the maxillary prominence in the domain of the maxillary nerve. Through comparative analysis using various tetrapods, we concluded that the palatine process should not be considered part of the ancestral premaxilla. It rather corresponds to the anterior region of the vomerine bone of nonmammalian tetrapods. Thus, the present findings indicate that the true premaxilla was completely lost during the evolution of the therian mammals, resulting in the establishment of the unique therian face as an evolutionary novelty. Reconsideration of the homological framework of the cranial skeleton based on the topographical relationships of the ossification center during embryonic development is warranted. Abstract : Therian mammals face was evolved through the drastic rearrangement of the embryonic primordia. The ancestral premaxillary region was changed into the semi‐motile nose, and the rostralmost upper jawbone "incisive bone" was newly established from the ancestral bones, septomaxilla and the anterior part of vomer. Research Highlights: The rostralmost jawbone, the incisive bone of therian mammals, was established by fusion of the septomaxilla and a part of the vomerine bone in the nonmammalian tetrapods. The true premaxilla was completely lost, and the corresponding region became the motile nose. These changes drove the evolution of the unique therian face.